36 A new anticancer drug in sinonasal carcinoma targeting the NFkB pathway. Issue 5 (May 2015) - ,; López-Hernández, A.; López, F.; Costales, M.; Vivanco, B.; Llorente, J.L.; Hermsen, M.
Abstract : Introduction: Sinonasal squamous cell carcinomas (SNSCC) are unusual head and neck tumours, etiologically related to occupational exposure to leather and wood dust as well as several industrial chemicals as nickel, asbestos and formaldehyde. However, tobacco smoking does not play an important role. Overall survival is poor, partly due to anatomical resection difficulties and the lack of response to existing chemotherapeutic schemes. Therefore, alternative treatment options are needed. We studied the efficacy of a new anticancer compound EC-70124, that possibly acts on the AKT and NFkB signalling pathways, with important roles in tumorigenesis. Material and methods: Five stable cell lines, set up in our lab from primary tumours of different disease stages and with different clinical behaviours, were used for in vitro study of the effects of EC-70124 on proliferation, invasion in matrigel, cell cycle and apoptosis. The genome-wide genetic profiles as well as protein expression status of AKT and NFkB were analysed both in cell lines and in their corresponding primary tumours. Results: EC-70124 inhibited cell proliferation with great differences between the five cell lines. There was no clear effect on apoptosis and cell cycle, however, invasion was strongly inhibited in two cell lines that highly expressed NFkB in the nucleus. Only one of the original primary tumours of these two cell lines also showed nuclear NFkB overexpression. Conclusions: EC-70124 has anticancer effect on sinonasal carcinomas by inhibiting proliferation and invasion, and the mechanism of action appears to involve the NFkB pathway.